Influence of Rehabilitation on Health of Ballroom Dancers After Sports Injuries - Adrianna Banio (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
The paper is aimed at assessing the influence of rehabilitation on health of ballroom dancers after sports injuries. At the turn of 2014 and 2015 ballroom dancers from all around Poland were questioned. The surveyed were professional dancers aged between 13 and 30 years. As many as 63 athletes were injured during their career. The rehabilitation of 47 of them took place in the rehabilitation centre under physiotherapeutic supervision. Only 16 of the injured rehabilitated on their own. The opinion poll based on the survey was used as a method. The questionnaire included closed and open questions which were to show the influence of injury and its treatment on future sports career. Questions were detailed and referred to the kinds of injuries and their causes, the process of treatment, duration of rehabilitation, its process and results. Questionnaire results were analysed statistically with the use of the Pearson’s chi-squared test. It has been proved that rehabilitation under physiotherapeutic supervision has positive influence on health of ballroom dancers after injuries. Specialist rehabilitation of sportsmen after sports injuries contributed to the shortening of time of the recuperation and to the complete recovery. The time of recovery of the injured who did not undergo the professional rehabilitation was longer, and it was impossible to restore lost functions in the group of 5% of the surveyed, which resulted in the end of their career. Dancers after sports injures should always undergo professional rehabilitation under the sports doctor’s and physiotherapist’s supervision.